Diversity of Fern Types (Pteridophyta) in The Grojogan Sewu, Parang Ijo, and Jumog Waterfall Tourist Areas of Karanganyar Regency - Sholikah, Siti Amaliatus; Muzzazinah , Muzzazinah (BIOEDUSCIENCE, 2025)
Background: The condition of the area in the three waterfall areas in Karanganyar Regency is very suitable for the growth of various organisms, both flora and fauna, especially ferns. These three areas have different environmental factors and regional topography, which allow various types of Pteridophyta to occur. This study aims to determine differences in fern diversity across three waterfall locations in Karanganyar Regency: Grojogan Sewu, Jumog, and Parang Ijo. Method: This research uses a purposive sampling method with plot and roaming techniques. Results: The research identified 35 terrestrial and epiphytic Pteridophyta, comprising 15 families and 6 orders: Polypodiales, Cyatheales, Gleicheniales, Lindseales, Salviniales, and Marattiales. The highest diversity index (H') and evenness (E) of ferns are found in the Parang Ijo Waterfall area, which are 2.14 and 0.71. The Parang Ijo Waterfall area has various environmental and topographic factors that support fern adaptation. The highest dominance index (C) is 0.51 in the Grojogan Sewu Waterfall area. Conclusion: The Grojogan Sewu Waterfall area has a more homogeneous and extensive habitat, thus supporting the dominant types of ferns to grow in large numbers.